The complete chloroplast genome of Scoparia dulcis (Plantaginaceae). Issue 1 (2nd January 2022) - Li, Lin-Xuan; Lin, Yang; Tang, Dan-Feng; Quan, Chang-Qian; Liang, Ying; Qin, Shuang-Shuang; Wei, Fan; Wei, Kun-Hua
Abstract: Here, we report the complete chloroplast genome of Scoparia dulcis L. The genome is 153, 701 bp in size. Two inverted repeats (IRs) with a total of 50, 546 bp were identified. The rest of the sequence was separated into two single-copy regions, including a large single-copy (LSC) region (85, 029 bp) and a small single-copy (SSC) region (18, 126 bp), respectively. The genome of S. dulcis comprised of 129 genes, including 85 protein-coding genes, 8 rRNA genes, and 36 tRNA genes. Phylogenetic analysis showed that S. dulcis was strongly allied with Bacopa monnieri.